Influência de um programa de exercício físico resistido em camundongos fêmea com doença de Alzheimer - Silva, Eduardo Alves Da [UNIFESP] (2019)
Alzheimer's disease is a neurodegenerative disease that primarily affects functions related to memory and cognition. The prevalence of the disease is higher in women than in men. The major brain regions affected during the course of AD are the hippocampus and the prefrontal cortex due to the deposition of beta-amyloid plaques (βA) and neurofibrillary tangles of hyperphosphorylated Tau protein. Considering cognitive deficits and the absence of an effective treatment for AD, physical activity has emerged as an alternative of complementary treatment to prevent or delay the progression of the disease. Although several studies with humans and animals show that aerobic exercise promotes important changes in the brain, the impact of resistive physical exercise on AD is not well understood. Objective: To verify the behavioral and morphological changes induced by physical resistance exercise in transgenic female mice for AD. Methodology: Female mice APPSWE/PS1dE9, amyloidogenic model and their respective wild Alzheimer negative, were distributed into 4 groups: Naive/Control and DA/Control (without training) and Naive/Exercise and DA/Exercise (submitted to resistance training protocol - climbing on ladder with weights) for four weeks. Locomotor and exploratory activity was analyzed by the open field test. The anxious type behavior was performed by the high cross maze test. Long-term memory (LTM) was evaluated by the object recognition test. The visualization of the deposition of βA plaques in the cortex and hippocampus was performed by the immunohistochemistry technique. Results: Resisted physical training progressively increased strength (p <0.01) and locomotor activity (p = 0.01) in Naive/Exercise and AD/Exercise groups. There was no difference in anxiety type behavior between the groups. The cognitive impairment (LTM) observed in Alzheimer's animals was reversed by the resisted physical exercise program (p <0.01). A significant reduction of βA plaques was observed in the motor cortex (p = 0.003) and in the dorsal hippocampus (p = 0.028) of animals with AD / exercise. Conclusions: The resistance training program was able to improve cognitive performance and to decrease the number of βA plaques in the hippocampus and in the cortex of mice with AD.